Lowering the limit: reducing the CD4 T-cell threshold for ophthalmic screening in patients with HIV in an ethnically diverse UK population - Morjaria R (Dove Medical Press, 2014)
Rupal Morjaria,1,2 Vaneeta Sood,1 Kaveh Manavi,1 Alastair K Denniston,1,3 Helen Palmer1 1Queen Elizabeth Hospital Birmingham, University Hospitals Birmingham National Health Service Foundation Trust, Birmingham, United Kingdom; 2Nuffield Department of Ophthalmology, Oxford University Hospitals National Health Service Trust, Oxford, United Kingdom; 3Centre for Translational Inflammation Research, University of Birmingham, Birmingham, United Kingdom Background: Before highly active antiretroviral therapy, cytomegalovirus (CMV) retinitis was a major threat to vision in individuals with HIV. We investigate whether ophthalmic screening of asymptomatic HIV patients still has value in the highly active antiretroviral therapy era and consider CD4 thresholds in line with the world literature and UK experience.Methods: A retrospective chart review was conducted of all patients seen by the HIV Ophthalmic Service of a UK university hospital both before (2007–2008) and after (2011–2012) introduction of a threshold of CD4 lower than 100 cells/mm3. Data collected included CMV and HIV RNA load, CD4 cell counts and CD4 percentage, CMV-immunoglobulin G status, ocular symptoms, and evidence of HIV-related ocular disease. Results: In total, 54 patients were referred to the HIV ophthalmic service. Three patients failed to attend, resulting in complete data for 51 patients (n=24 for 2007–2008; n=27 for 2011–2012). Seven patients had ophthalmic manifestations of their HIV; these cases had lower CD4 counts than those with normal examinations (median [interquartile range], 9 [7–80] versus 175 [44–394]; P=0.0039; Mann–Whitney test). Six cases had HIV retinopathy without sight loss; one case had sight-threatening CMV retinitis associated with a CD4 count of 6 cells/mm3. Conclusion: Before 2008, our practice was to screen all asymptomatic patients with CD4 counts lower than 200 cells/mm3. Screening asymptomatic patients with CD4 counts below 100 cells/mm3 was not associated with any missed or late-presenting cases of CMV retinitis in our HIV population. Keywords: cytomegalovirus retinitis, HIV, HAART